2018
DOI: 10.1186/s12885-018-4600-6
|View full text |Cite
|
Sign up to set email alerts
|

MASTL inhibition promotes mitotic catastrophe through PP2A activation to inhibit cancer growth and radioresistance in breast cancer cells

Abstract: BackgroundAlthough MASTL (microtubule-associated serine/threonine kinase-like) is a key mitotic kinase that regulates mitotic progression through the inactivation of tumor suppressor protein phosphatase 2A (PP2A), the antitumor mechanism of MASTL targeting in cancer cells is still unclear.MethodsMASTL expression was evaluated by using breast cancer tissue microarrays and public cancer databases. The effects of MASTL depletion with siRNAs were evaluated in various breast cancer cells or normal cells. Various me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 31 publications
5
57
0
Order By: Relevance
“…2a). Furthermore, we found that CD44 high /CD24 low MCF7 cells, a breast cancer stem cell line with a radioresistant phenotype 24,25 ( Supplementary Fig. S2), expressed higher levels of p-S6K1 compared to those of control MCF7 cells ( Fig.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…2a). Furthermore, we found that CD44 high /CD24 low MCF7 cells, a breast cancer stem cell line with a radioresistant phenotype 24,25 ( Supplementary Fig. S2), expressed higher levels of p-S6K1 compared to those of control MCF7 cells ( Fig.…”
Section: Resultsmentioning
confidence: 89%
“…All media were supplemented with 10% foetal bovine serum (Corning) and 1% penicillin/streptomycin, and maintained in a humidified 5% CO 2 incubator at 37 °C. Radioresistant CD44 high /CD24 low MCF7 cells were established using a previously described method 24,25 . In brief, CD44 + /CD24 − subpopulations from MCF7 cells were isolated according to their surface markers with flow cytometry using a FACS Aria II system (BD Biosciences, San Diego, CA, USA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clonogenic assay. The clonogenic assay was performed as described previously 7,10,35 . MCF-7 or BT-549 cells (500 in number) were seeded on a 22 mm plastic coverslip in a 6-well plate for 24 hrs.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…After this, mean SSC-A value in PI-negative population was quantified and relative Mean SSC-A values were calculated based on none-vehicle. Cell cycle analysis was performed following the method previously described 35 . Briefly, the cells treated with TTFields or TTFields and BTNP for 72 hrs were trypsinized, washed twice in PBS, and fixed with ice-cold 70% ethanol.…”
Section: Facs Analysismentioning
confidence: 99%